Experiment, modeling and simulation of bypassing holes in composites. (15th February 2020) - Hartmann, Stefan; Kheiri Marghzar, Ali; Gilbert, Rose Rogin; Pangboonyanon, Woramon; Meiners, Dieter
Abstract: This article discusses modeling aspects of fiber circumplacement around a hole using continuous functions. Here, spatially inhomogeneous transversal isotropy is formulated on the basis of patches using B-spline approaches generating the fiber orientation. For this purpose, experiments with different fiber orientations and "hole"-concepts are provided for both the identification of material parameters as well as for model validation. The validation examples are a plate with uniform fiber distribution, where the hole is drilled after the production process, and a plate with circumplacement around the hole, where the fibers are bypassed before the matrix material is injected. The entire numerical problems are treated using finite elements. Furthermore, the material parameters are identified using – within a least-square approach – the combination of finite element simulations and optical results of a digital image correlation system.